2012
DOI: 10.1177/1059840512461282
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use Among Sexually Active Rural High School Adolescents Personal, Environmental, and Behavioral Predictors

Abstract: Adolescents who engage in unprotected intercourse are at risk of pregnancy and sexually transmitted infection (STI). Although adolescents in rural areas participate in levels of sexual risk taking similar to that of nonrural youth, few data are available identifying factors that influence condom use among rural adolescents. The purpose of this study is to determine the predictive value of selected personal, environmental, and behavioral factors for condom use among rural adolescents in grades 9-12. A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 51 publications
4
21
1
1
Order By: Relevance
“…37,41 The same procedure was used to handle the three studies that reported both general contraceptive use and condom use. 17,43,44 Specifically, we averaged the effect of communication on these sexual health outcomes for primary analyses, but we used a random number generator to select one outcome variable from each study when we examined the type of outcome (contraceptive use vs. condom use) as a moderator. 37,41 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,41 The same procedure was used to handle the three studies that reported both general contraceptive use and condom use. 17,43,44 Specifically, we averaged the effect of communication on these sexual health outcomes for primary analyses, but we used a random number generator to select one outcome variable from each study when we examined the type of outcome (contraceptive use vs. condom use) as a moderator. 37,41 …”
Section: Methodsmentioning
confidence: 99%
“…3,912 While several studies have found moderate, positive associations between parent communication and youth contraceptive or condom use, 13–16 other studies have found non-significant or even negative effects. 1719 Further, while it is possible that parental communication about sex can be protective for youth, open sexual communication often does not take place. Instead, embarrassment, inaccurate knowledge, or low self-efficacy may prevent some parents from engaging their children in honest and supportive conversations about sex.…”
Section: Introductionmentioning
confidence: 99%
“…Findings vary when self-efficacy includes or is solely defined by condom mechanics. Among rural White adolescents, self-efficacy that includes both negotiation and mechanics is correlated with but is not predictive of condom use (Haley et al, 2012). Sexual risk-reduction interventions that have targeted increasing condom mechanics self-efficacy in CHS youth are limited and have shown either short-term marginal significance (Coyle et al, 2013) or significance for the control group only (Coyle et al, 2006).…”
Section: Peermentioning
confidence: 98%
“…It includes negotiating condom use with a sexual partner and the mechanics of placing a condom (Brafford & Beck, 1991). Persons with greater self-efficacy for condom use (Haley et al, 2012;Shneyderman & Schwartz, 2012) or condom negotiation (Crosby et al, 2013) are more likely to report condom use. For Latinos, embracing Latino cultural values (a distal construct of acculturation) is associated with greater condom use-self-efficacy whereas identifying more with American cultural values is related to less condom use (Ma et al, 2014).…”
Section: Peermentioning
confidence: 99%
See 1 more Smart Citation